Taxpayers perception on electronic fiscal devices (EFDS): A case of Dar es salaam. - Zaburi, Akimu (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirements for the degree of Masters of Corporate Management of Mzumbe University.